Wear analysis of PM compacts with bainitic microstructures, under unlubricated sliding conditions - Steimbreger, Ceferino (2015)
Ferrous and non-ferrous alloys can be processed by PM. Complex shapes and good surface finishes can be achieved, leading to promising applications, if mechanical properties are demonstrated to be high enough. At the same time, both bainitic and carbide free bainitic microstructures have proved to be excellent candidates for wear applications. Therefore, the aims of this project were steered towards analysing wear behaviour of PM compacts, in relation to their bainitic microstructures.Three materials were employed and two conditions were taken into account: materials before and after austempering. A reference material was considered, corresponding to Distaloy DC with Mo and Ni. Microstructure was analysed in all the cases by means of optical and scanning electron microscope and it was related to the behaviour observed. Pin on plate reciprocating sliding test without lubricant was utilised in order to measure friction coefficient and specific wear rate in the pins. Effects of alloying elements were also examined.It was found that austempering decreased impact resistance, but enhanced hardness in Distaloy DC. In contrast, the other two materials presented the opposite behaviour. However, the presence of additional alloying elements in the initial composition fulfilled to increase wear resistance, compared to the reference material. A possible interaction between pores and oxides that may influence wear behaviour was observed. Si allowed carbide free bainitic microstructure to form but heterogeneity could not be prevented. Therefore, the advantage of this microstructure could not be fully used. Results obtained in the present work can lead to new wear applications for PM products, containing bainitic microstructures.